Antihypoxic, nephroprotective and antioxidant properties of hydro-alcoholic extract of loquat flowers - Nabavi, Seyed Fazel; Nabavi, Seyed Mohammad; Hajizadeh Moghaddam, Akbar; Hellio, Claire; Ebrahimzadeh, Mohammad Ali (Progress in Nutrition, 2015)
Objectives: Loquat is well known Chinese medicinal herb with numerous traditional usages. The fact of the promising effect of loquat on different diseases is approved by a plethora of recent studies. Methods: In the present study antihypoxic, antioxidant and nephroprotective activity of hydro-alcoholic extract of Eriobotrya japonica flower was an investigated employing different in vivo and in vitro assay system. The chemical analysis of Eriobotrya japonica flowers, using atomic absorption spectroscopy, highlighted the presence of eight elements. Gallic acid, rutin and quercetin were determined by HPLC/DAD. Results: Results indicated that the hydro-alcoholic extract has a protective effect against hypoxia induced lethality in mice. Extract at doses of 200 and 400 mg/kg/day for 10 consecutive days, i.p. gave nephroprotection by changing blood urea nitrogen (BUN), serum urea and creatinine levels. Extract showed good antioxidant and antihemolytic activity in all studied models. Present study demonstrates hydro-alcoholic extract of Eriobotrya japonica as a plant with high biological properties. Conclusion: In conclusion, loquat flowers are potential sources of antioxidant, anti-hypoxic and nephroprotective agents.